2023
DOI: 10.3389/fhort.2023.1120267
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of polyphenolic compounds in two different cultivars of marigold (Tagetes erecta L.) using high-performance thin-layer chromatography

Abstract: Marigold (Tagetes erecta L.), a popular ornamental plant of the family Asteraceae, is commonly cultivated in many countries, including India, for its decorative flowers. The plants grow easily in a variety of soil and climatic conditions and have been reported to damage the nematode population of soil and control indirectly harmful microbes. High-performance thin-layer chromatography (HPTLC) was utilized in the present study, with a view to identify some important biologically active compounds in the flowers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
1
0
1
Order By: Relevance
“…Вид Tagetes erecta L. відноситься до культивованих та об'єднує велику кількість сортів, які відрізняються за морфологічними характеристиками та складом біологічно активних речовин. Внутрішньовидові відмінності у хімічному складі чорнобривців прямостоячих всебічно досліджуються [10]. При цьому менше уваги приділено вивченню компонентному складу та вмісту жирних кислот сортів роду Tagetes L.…”
Section: вступunclassified
“…Вид Tagetes erecta L. відноситься до культивованих та об'єднує велику кількість сортів, які відрізняються за морфологічними характеристиками та складом біологічно активних речовин. Внутрішньовидові відмінності у хімічному складі чорнобривців прямостоячих всебічно досліджуються [10]. При цьому менше уваги приділено вивченню компонентному складу та вмісту жирних кислот сортів роду Tagetes L.…”
Section: вступunclassified
“…These activities could be associated with various chemical components including carotenoids [ 7 ] and polyphenols [ 6 ]. Some authors have identified lutein (a carotenoid) and laricitrin (a flavonoid) as the main chemical structures abundant in T. erecta and responsible for its biological activities [ 8 ].…”
Section: Introductionmentioning
confidence: 99%